INTEGRATION EXTENT OF UKRAINE IN INTERNATIONAL MULTI-LAYER FLIGHT SAFETY CONTROL SYSTEM - Куклінський, М.В.; Холявкіна, Т.В. (Proceedings of National Aviation University, 2012)
Flight Safety is one of the main areas of civil aviation. Orderly approach to flight safety provision, including necessary organizational structures, sphere of responsibility, policy and procedures represents a multi-layer System for Flight Safety Control (SFSC). Ukraine, as aviation country, to a certain extent is already integrated into all the SFSC levels, but the question remains open – how deep this integration is accomplished, and also problems that impede it. By means of analysis for each of the levels, it was shown that more deep integration is made on low levels, but the higher levels did not demonstrate such tendency. The situation can be corrected by more clear and coordinated reforms directed to cooperation with European agencies in the field of flight safety provision.